Work values of undergraduates in Malaysia: a comparison across various programs of study and gender - Abdul Hamid, Jamaliah; Omar, Zoharah; Othman, Jamilah; Alby, Jeffrey Lawrence D'Silva; Abdul Wahat, Nor Wahiza (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Recent university graduates have grown up in a more affluent and market-oriented economic environment, and consequently their work values are likely to be different from the earlier generations. A recent study has shown that the young generation tends to adopt more competitive and proactive attitudes toward work (Hirschi, 2010). Also, there are studies on the gender influence on work values. Many gender differences in work values are due to the influence of normative social expectations at home and in social context. People are socialized to behave in gender-appropriate manner at the work place, and they are exposed to multiple dimensions of work values which are gender-associated. Consequently, they develop their perceptions of appropriate work values associated with their own family background, peers, and other influential role models (Gottfredson 1981, Eagly 1987).Already a substantial amount of research has been done to identify sources of gender differences in work values (Chusmir & Parker 1991, Nieva & Gutek 1981). This article is an exploratory analysis of a study on the work values asprired by contemporary university undergraduates in various faculty programs of study, with gender as a chosen base factor of comparison.